Opportunistic validation of sulfur dioxide in the Sarychev Peak volcanic eruption cloud - Carn, S. A.; Lopez, T. M. (Atmospheric measurement techniques, 2011)
We report attempted validation of Ozone Monitoring Instrument (OMI) sulfur dioxide (SO2) retrievals in the stratospheric volcanic cloud from Sarychev Peak (Kurile Islands) in June 2009, through opportunistic deployment of a ground-based ultraviolet (UV) spectrometer (FLYSPEC) as the volcanic cloud drifted over central Alaska. The volcanic cloud altitude (~12–14 km) was constrained using coincident CALIPSO lidar observations. By invoking some assumptions about the spatial distribution of SO2, we derive averages of FLYSPEC vertical SO2 columns for comparison with OMI SO2 measurements. Despite limited data, we find minimum OMI-FLYSPEC differences within measurement uncertainties, which support the validity of the operational OMI SO2 algorithm. However, our analysis also highlights the challenges involved in comparing datasets representing markedly different spatial and temporal scales. This effort represents the first attempt to validate SO2 in a stratospheric volcanic cloud using a mobile ground-based instrument, and demonstrates the need for a network of rapidly deployable instruments for validation of space-based volcanic SO2 measurements.